Off-pump coronary artery bypass surgery in a patient with dextrocardia and situs inversus totalis: a case report - D. Yu. Kozmin; S. T. Enginoev; G. M. Magomedov; I. I. Chernov (Российский кардиологический журнал)
The article discusses a rare clinical case of successful off-pump coronary artery bypass surgery in a patient with dextrocardia and situs inversus totalis (SIT). SIT is a rare condition in which the arrangement of the internal organs is a mirror image of normal anatomy.